Integrating Canva as Teaching Media and Project Based Learning Tool in Language Teaching - Jalu Harsabawa (UM Purwokerto Press, 2023)
Due to the pandemic condition, teachers are forced to adapt with the condition where Digital technology are heavily involved in the process of teaching and learning. Digital application with the feature of online meeting and Management system are become the main spotlight for teacher. Through Canva, teacher can assign their students to working on the project together with their friend. Several things need to be considered in using Canva are; it is heavily dependent on internet connection and because Canva is not an application that create for education purpose alone. so, teachers will have to use their creativity in integrate it with their teaching and learning activity which might need more effort than using the application which solely create for educational purpose. In short, Canva is digital application which create for creating and designing but it also can be used in teaching and learning activity. It is dependent on the teacher on how they will use it.